The Relationship of Learning Interest and Engineering Images Learning Outcomes with Forming and Assembly Learning Results in Class XI Metal Fabrication Engineering Expertise Program SMKN 1 Lubuk Pakam - Efendi, Hidir; Syahputra, Dedi (Journal of Community Research and Service, 2023)
The purpose of this research is to (1) establish a connection between student enthusiasm in learning and subsequent achievement in forming and assembling the connections between (2) learning outcomes in engineering drawings and (3) learning outcomes in formation and assembly, and (3) learning motivation and engineering drawing and formation and assembly outcomes. The 36 participants in this study were all students from Class XI at SMK Negeri 1 Lubuk Pakam who were majoring in Metal Fabrication Engineering. Students from Class XI at SMK Negeri 1 Percut Sei Tuan were used to test the instrument before it was administered to the research sample. Correlational analysis is the approach of choice for this study. First, a 0.719 correlation coefficient and a 0.517 coefficient of determination indicate that students' motivation to learn is associated with their success in forming and assembling knowledge. This suggests that curiosity accounts for 51.7% of the variance in the results of exercises involving group formation and assembly. The coefficient of determination is 0.000, which is less than 0.05, and statistically significant. The learning outcomes for engineering drawing and forming and assembling are significantly related to one another, with a correlation value of 0.598 and a coefficient of determination of 0.358, respectively. This means that the knowledge gained from studying technical drawings is crucial to the achievement of 35.8 percent of the knowledge gained from studying construction and fitting. The coefficient of determination is 0.000, which is less than 0.05, and statistically significant. Learning results for technical drawing and forming and assembly skills are positively related to student interest in learning, as shown by the regression equation Y=33.355+0.507 X_1+0.297 X_2. The outcomes of learning about forming and assembly processes were found to have a substantial association with the outcomes of learning about engineering drawings. The F value of 21.021 indicates this, and it is more than the cutoff value of 3.28 in the F table, therefore the F test supports this interpretation. Thus, for students in class XI of the Metal Fabrication skill program at SMK Negeri 1 Lubuk Pakam, there is a positive and statistically significant association between interest in learning and learning outcomes of technical drawing and learning outcomes of forming and assembly.